Impact of the COVID-19 Pandemic on Hunger and Food Security (International relations and international law Journal, 2022)
This article analyzes the impact of the COVID-19 pandemic on hunger and food security. The rapid spread of the coronavirus has disrupted an already fragile global food system. Prior to the pandemic, global hunger was on the rise due to socio-economic factors, natural disasters, military conflicts and climate change. Food security problems have taken on alarming proportions due to the introduced restrictive measures to prevent the spread of COVID-19.The article examines the vulnerabilities of modern food systems and the reasons for the rapid rise in the level of world hunger. The article considers modern indicators of hunger, which are not able to fully give an adequate assessment of the state of the level of world hunger. An overview of financial support and measures to stimulate the economy from the government and world financial institutions is given. In the context of COVID-19, there is a need to improve the technology of tillage, harvesting and supplying them to wholesale and retail markets. Within the framework of this article, the need to introduce green energy is considered, which is dictated by the current state of the planet and the improvement of hunger assessment systems.Key words: food security, COVID-19, pandemic, hunger, food systems, economy, hunger indicators.